DEVELOPING ENGLISH LEARNING MATERIALS FOR NURSING STUDENTS OF BORNEO UNIVERSITY OF TARAKAN - Uli Agustina Gultom (LingTera, 2016)
This study aimed to develop appropriate English learning materials for nursing students of Borneo University of Tarakan in learning English. This study was a Research and Development (R D) study. The steps of the study were conducting needs analysis, writing the course grid, developing the materials, getting validation and revising the materials, trying out the materials, evaluating the materials, and writing the final draft of the materials. In this study, the data were collected by using needs analysis questionnaire, materials evaluation questionnaire and an interview guideline.  Four units were developed in this study. Each unit consisted of 12 until 15 tasks that were organized into Lead-in, Lesson Proper, Homework, Evaluation, Reflection and Word Bank. The data analysis showed that the developed materials were appropriate. The range of the mean value was 3.12 to 3.64. Referring to the quantitative data conversion, the range was in the good category. The data also suggested that the appropriate learning materials for nursing students had some components: goals, input, procedures, setting, teacher roles and learners roles.